2009
DOI: 10.1364/ol.34.003875
|View full text |Cite
|
Sign up to set email alerts
|

Dual-comb electric-field cross-correlation technique for optical arbitrary waveform characterization

Abstract: We present an electric-field cross-correlation technique that uses a pair of frequency combs to sweep phase and group delays independently without a mechanical stage. We demonstrate this technique for characterization of optical arbitrary waveforms composed of ~30 spectral lines from a 10 GHz frequency comb. Rapid data acquisition (tens of microseconds) enables interferometric spectral phase measurement of pulses subject to propagation over 20 km of optical fiber.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…Also, real-time spectrograms are produced along-side high-resolution soliton trajectories. These features are derived by adapting coherent linear optical sampling 44 and electric-field cross-correlation 45 to the problem of microcavity soliton imaging. Beyond the necessity to employ a new method for imaging soliton motion in microcavities, the high-repetition rate of microcavity solitons (tens of gigahertz and higher) is advantageous in sampling-based recording of motion.…”
Section: Introductionmentioning
confidence: 99%
“…Also, real-time spectrograms are produced along-side high-resolution soliton trajectories. These features are derived by adapting coherent linear optical sampling 44 and electric-field cross-correlation 45 to the problem of microcavity soliton imaging. Beyond the necessity to employ a new method for imaging soliton motion in microcavities, the high-repetition rate of microcavity solitons (tens of gigahertz and higher) is advantageous in sampling-based recording of motion.…”
Section: Introductionmentioning
confidence: 99%
“…Upon photodetection, the mixing of two optical frequency combs (OFCs) with different mode spacings produces a frequency comb in the radio frequency (RF) domain which retains the amplitude and phase information of both OFCs [3]. If one of the two OFCs acts as a reference with flat spectral phase, the spectral phase of the RF comb directly mirrors that of the test comb, which can then be mapped to the optical spectrum and Fourier transformed to produce the comb's time-domain waveform [4]. Recently, it has been demonstrated that by considering a larger portion of the RF comb, a self-referenced measurement of each optical comb can be recovered, thus eliminating the need for a known reference with flat phase [5].…”
Section: Introductionmentioning
confidence: 99%
“…Parallel processing is possible by using the AWG, which is expected to be a powerful tool in future high-speed information processing with an optical pulse synthesizer. Although the cross-correlation technique with a pair of combs [12] can measure the amplitude and phase spectra with a compact system, the time resolution is limited by the scanning center frequency range.In this Letter, an ultrafast OFC synthesizer and analyzer for generating and analyzing arbitrary waveforms in the THz range is proposed. Such a high-speed waveform can be generated using an OFC whose frequency band is proportional to its speed.…”
mentioning
confidence: 99%
“…Parallel processing is possible by using the AWG, which is expected to be a powerful tool in future high-speed information processing with an optical pulse synthesizer. Although the cross-correlation technique with a pair of combs [12] can measure the amplitude and phase spectra with a compact system, the time resolution is limited by the scanning center frequency range.…”
mentioning
confidence: 99%